2018
DOI: 10.4049/jimmunol.1701690
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Immunoreactive Levels of IgG4 Correlate with Clinical Responses during the Maintenance Phase of House Dust Mite Immunotherapy

Abstract: Allergen-specific immunotherapy for house dust mite allergy is effective, but there are no validated biomarkers reflecting or predicting the clinical efficacy. We aimed to investigate the relationship between clinical outcomes and functional responses of allergen-specific IgG4 (sIgG4) and specific IgE (sIgE) during s.c. allergen immunotherapy (SCIT) in allergic rhinitis and/or asthma patients. Combined symptom medication scores (SMS),-sIgG4 levels, -sIgE levels, and the serum inhibitory capacity against-sIgE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
7
42
0
Order By: Relevance
“…We found that SCIT can effectively relieve allergic symptoms and reduce the use of rescue drugs (P < 0.05), resulting total effective rate as 84.21%. Artemisia-sIgG4 increased significantly after SCIT, and had a moderate correlation with treatment duration (r = 0.558, P < 0.01), consistent with former studies which reported allergen specific IgG4s could increase in time-dependent manner [10,25] during AIT. Allergen specific IgG4s are bispecific antibodies that may block antigenic epitopes and act as blocking antibodies and it may be responsible for postimmunotherapy serum inhibitory for IgE [12].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that SCIT can effectively relieve allergic symptoms and reduce the use of rescue drugs (P < 0.05), resulting total effective rate as 84.21%. Artemisia-sIgG4 increased significantly after SCIT, and had a moderate correlation with treatment duration (r = 0.558, P < 0.01), consistent with former studies which reported allergen specific IgG4s could increase in time-dependent manner [10,25] during AIT. Allergen specific IgG4s are bispecific antibodies that may block antigenic epitopes and act as blocking antibodies and it may be responsible for postimmunotherapy serum inhibitory for IgE [12].…”
Section: Discussionsupporting
confidence: 90%
“…Allergen specific IgG4s are bispecific antibodies that may block antigenic epitopes and act as blocking antibodies and it may be responsible for postimmunotherapy serum inhibitory for IgE [12]. By ELIFAB, it was found that serum inhibitory activity for IgE increased significantly after SCIT (P < 0.05) and correlated moderately with levels Table 2 Sensitization of AR-sIgG4 (r = − 0.501,P < 0.01), as in former studies [10,11]. However, there is no significant relationship between serum inhibitory activity for IgE and clinical improvements, which is different from what have been reported.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…To our knowledge, we must note there is no head‐to‐head comparison of these different approaches. Although there are no clearly identified surrogate markers to monitor the benefits of AIT, there is now a growing consensus that blocking activities of allergen‐specific IgG4 antibodies correlates with the improvement of the clinical symptoms (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Functional activities of IgG can assess with IgE-facilitated allergen binding to B cells (IgE-FAB) which measures the serum inhibitory capacity. In addition to this flow cytometry-based assay, it can be measured with a fluorescent immunoassay which is called Immunosolid-phase allergen chip (ISAC) [88,89]. This method contains immobilization of allergens on a microarray chip which allows simultaneous measurement of specific IgE antibodies to allergen sources, and allergen-specific IgG and IgG 4 measurements.…”
Section: Observing Total Ige Allergen Specific Ige and Igg4mentioning
confidence: 99%